High efficient solar photocatalytic carbon nanoparticles - Flores-Oña, Diego; Fullana, Andres (Frontiers in Catalysis, 2022)
In the present study, the photocatalytic activity of carbon nanoparticles (CNPs) in the degradation of methylene blue (MB) using sunlight was analyzed. The CNPs were synthesized by solvent-assisted hydrothermal carbonization (HTC) and were characterized by various spectroscopic techniques: TEM and SEM microscopy, UV-Vis, FTIR, Fluorescence, and XPS. By changing the conditions of the HTC process, the surface chemistry of CNPs was functionalized, thus a great quantity of oxygenated functional groups was generated, which eventually influenced the photocatalytic process. Next, tests were carried out with different types of nanoparticles, varying the concentration of the dye and the type of light used in the irradiation. As a result of this, more than 93% of MB degradation was achieved in 20 minutes of irradiation using sunlight. This result is promising since it has not been achieved by other nanomaterials. This research can be a potential starting point for the development of new solar photocatalysts.